Projetos de viabilidade econômica e financeira para a produção do desenvolvimento econômico e regional: análise dos projetos realizados pela empresa N. M. Figueira Consultoria e Projetos - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The objective of this work is to analyze the importance of the project of economic and financial viability for the promotion of regional economic development, based on the projects of expansion, modernization and implementation carried out by the company N. M. M. Figueira Consultoria e Projetos. To meet the objectives, the methodology used is based on bibliographic research through articles, bulletins and books, to build the theoretical contribution. In this sense, it can also be considered as qualitative research, in which it analyzed the experiences/portfolio of projects of the company N. M. M. Figueira Consultoria e Projetos. In addition, data were collected from official websites in order to characterize the panorama of the municipality of Santarém and the region about its productive activities. From the analysis of the data of the aforementioned company, 112 projects approved and implemented from the year 1998 to 2021 were investigated, which in turn, it was found that these generated positive economic and social impacts for the municipality of Santarém and adjacent municipalities, such as job creation, injection of resources into the local economy, thus promoting, the development of the region. However, the implementation of economic and financial projects still faces obstacles to their submission and permanence of positive results, caused by the characteristics of the region and the rigor of project analysis through financial institutions.
Keywords: Projetos econômico-financeiros; Desenvolvimento regional; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS